Intradural lumbar disc herniation of L2–L3: A case report and literature review - Chen, Xipeng; Cheng, Yuanpei; Wu, Han (Frontiers in Surgery, 2023)
Background: Intradural lumbar disc herniation (ILDH), especially upper lumbar intradural disc herniation, is a rare type of lumbar disc herniation (LDH). However, it may have severe and complex symptoms, causing serious impact on the patients. Additionally, it is difficult to be diagnosed with limited experience. Few studies on L2-L3 ILDH have been reported in the literature. This study presents such a case and reviews the incidence, etiology, symptoms, diagnosis and treatment of this disease, so as to provide guidance and experience for clinicians. Case presentation: A 27-year-old male patient had a one-month history of severe lower back pain and left lower extremity weakness after lumbar sprain. He could not walk due to progressive symptoms. Physical examination revealed that straight leg raising and femoral nerve stretch tests on the left side were positive. Magnetic resonance imaging of lumbar showed an intradural disc protruding into the ventral dural sac at the L2–L3 level. He was diagnosed ILDH of L2-L3, finally. An urgent operation was performed to remove the intradural disc fragment. The patient’s symptoms improved significantly, postoperatively. After eight months of follow-up, he returned to normal life with only slight lower back pain. Conclusions: ILDH at the L2-L3 level is an extremely rare type of LDH. Its diagnosis often requires a combination of symptom, physical examination, and imaging examination due to no typical symptoms or imaging features. A detailed preoperative plan including the definition of the position, calcification, migration, and adhesion of intradural intervertebral discs to decrease the risk of surgery, prevent the occurrence of complications, and promote postoperative prognosis of patients.